Recurrent Hyperammonemic Encephalopathy in Adults with Citrin Deficiency: A Case Report of Two Genetically Confirmed Cases - Tram Nguyen Que Pham; Van Huy Vo; Qui Huu Nguyen; Thuy Thi Thanh Trinh; Thong Duy Vo (Journal of Clinical Medicine, 2026)
Background: Adolescent and adult citrin deficiency (AACD), formerly known as adult-onset citrullinemia type II, is a rare autosomal recessive disorder caused by biallelic pathogenic variants in SLC25A13. It is an underrecognized cause of recurrent hyperammonemic encephalopathy, particularly when hepatic function is relatively preserved. Methods: We report two unrelated Vietnamese young men, aged 21 and 18 years, who presented with recurrent neuropsychiatric episodes. Clinical, biochemical, imaging, electrophysiological, and genetic findings were evaluated; whole-exome sequencing findings were confirmed by Sanger sequencing. Results: Both patients had long-standing preferences for protein- and fat-rich foods and avoidance of carbohydrate-rich foods, together with episodic hyperammonemia (345.21 and 103.07 µmol/L during symptomatic episodes). The first patient had a history of neonatal jaundice, mild cirrhosis, and severe behavioral disturbances, whereas the second was markedly lean and had no structural liver disease. Acquired causes of hyperammonemia and portosystemic shunting were excluded. Both patients harbored the homozygous pathogenic SLC25A13 variant NM_014251.3.852_855del (p.Met285ProfsTer2). Ammonia-lowering therapy and a low-carbohydrate, protein- and fat-enriched diet supplemented with medium-chain triglycerides resulted in clinical improvement, with no recurrent encephalopathic episodes during 6 months of follow-up in either patient. Conclusions: AACD should be considered in adolescents and adults with otherwise unexplained recurrent hyperammonemic encephalopathy, especially when ammonia elevation is disproportionate to liver disease. Characteristic dietary preferences provide an important diagnostic clue, and molecular testing enables definitive diagnosis and timely management.